Language Used by Female and Male in “Free Guy” Movie by Shawn Levy: Sociolinguistics Study - Ricka Maylani; Dianita Dianita (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this research is to examine the female and male language used in the film "Free Guy." Diagrams depicting the data frequency of appearance in each category are used to support this qualitative study research. The data is taken from utterances by characters in “Free Guy”. The source of data collection in this research shows that there are seven types of female language in “Free Guy” movies. The result of the research demonstrates that there are seven types of female language such as adverbs (4), adjectives (15), color words (2), diminutives (2), expletive and swear statements (6), tag questions (2), and modulation (8). On the other hand, there are five types of male language in “Free Guy” movies such as back-channeling signals (14), adverbs (9), expletive and swear statements (16), imperative sentences (8), and modulation (1). Expletive and swear statements are the most frequently used types of language by both female and male characters in the film "Free Guy." The researcher discovered 6 female languages swear statements and 16 male languages swear statements. In addition, there are 3 claims of female and male voices such as biologically different, social organization, and social creatures (learn how to act).